2019
DOI: 10.1016/j.jtcvs.2019.01.140
|View full text |Cite
|
Sign up to set email alerts
|

Complete unroofing of the intramural coronary artery for anomalous aortic origin of a coronary artery: The role of commissural resuspension?

Abstract: Objectives: Although surgical repair of an anomalous aortic origin of the coronary artery has low operative mortality, longer-term risk of ischemia and aortic regurgitation remains concerning. We routinely perform aortic commissure resuspension after unroofing and sought to evaluate the outcomes with regard to aortic valve competence, symptoms, and signs of ischemia with this approach. Methods: Twenty-six consecutive patients who received the unroofing procedure for anomalous aortic origin of the coronary arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 20 publications
1
12
0
1
Order By: Relevance
“…Last, the detached commissure is suspended above the unroofed intramural segment with pledgeted suture(s) ( Figure 5A ). Commissural resuspension is a technique that may lower the rate of aortic valve regurgitation and does not add any proven additional risk to the procedure ( 29 ). Alternatively, when the intramural coronary segment courses below the sino-tubular junction, a “neo-ostium” can be created in the correct sinus, at the point where the coronary artery emerges from the aortic wall ( Figure 5B ).…”
Section: Operative Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…Last, the detached commissure is suspended above the unroofed intramural segment with pledgeted suture(s) ( Figure 5A ). Commissural resuspension is a technique that may lower the rate of aortic valve regurgitation and does not add any proven additional risk to the procedure ( 29 ). Alternatively, when the intramural coronary segment courses below the sino-tubular junction, a “neo-ostium” can be created in the correct sinus, at the point where the coronary artery emerges from the aortic wall ( Figure 5B ).…”
Section: Operative Techniquesmentioning
confidence: 99%
“…Also, when detaching and then resuspending the commissure, the aortic valve regurgitation remains at risk. Last, the recent recognition of the intercoronary pillar is of some interest, a thickening of the aortic wall above the commissure, as a possible contributor to both pathophysiology of AAOCA and aortic valve support ( 29 ). The intercoronary pillar is the aortic wall segment above the intercoronary commissure, usually thicker than the remaining wall.…”
Section: Operative Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Resuspension should be performed regardless of whether or not aortic valve commissural detachment was performed, as it is crucial to securely resuspend the commissure to prevent late aortic insufficiency. Yerebakan and colleagues 8 recently reported that a modified unroofing technique with routine commissural resuspension was associated with a lower rate of aortic regurgitation (AR).…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…Studies have shown that the right coronary artery is more involved in the incidence of AAOCA than the left coronary artery [3]. However, AAOCA involving the left coronary artery carries a higher risk [4].…”
Section: Introductionmentioning
confidence: 99%